A new design of Microstrip hash-shape nanoantenna & Microstrip hash-shape slot nanoantenna at THz spectroscopy for imaging application - Raoof Mohammed Ali, Bassam; Jaafar Alyasiri, Abdulkadhum; Mohammed Ali, Faris (International Journal of Engineering and Technology, 2019)
The terahertz (THz) lies between electronics and optics frequency range, and THz frequencies are the lowest frequencies in which free space conventional optics can still be used before microwave components take over. The development of Terahertz technology systems led to focus of researchers on this technology field. In this paper, the CST Microwave studio 2018 is used to design and simulate a new Microstrip Hash-shape Nanoantenna (MHNA) & Microstrip Hash-shape Slot Nanoantenna (MHSNA). Gain, Directivity, Half Power Beamwidth, Return loss and Bandwidth are computed. The results of work achieved a frequencies in Terahertz in the case of Nano size. The first design and the second design operating in the range of (125.3 THz to 133.4 THz) and (126.4 THz to 133 THz) respectively. Where utilize a Gold in the patch and Ground plane, while, the Silicon material is utilize as substrate which having dielectric material (εr=11.9). Therefore the utilized of these bands of THz frequencies that referred to the millimeter, micrometer for spectroscopy for imaging applications.